2017
DOI: 10.3389/fmicb.2017.01387
|View full text |Cite
|
Sign up to set email alerts
|

The Cyanobacteria-Dominated Sponge Dactylospongia elegans in the South China Sea: Prokaryotic Community and Metagenomic Insights

Abstract: The South China Sea is a special reservoir of sponges of which prokaryotic communities are less studied. Here, a new record of the sponge Dactylospongia elegans is reported near the coast of Jinqing Island in the South China Sea, and its prokaryotic community is comprehensively investigated. Sponge specimens displayed lower microbial diversity compared with surrounding seawater. At the phylum level, prokaryotic communities were consistently dominated by Proteobacteria, followed by Cyanobacteria, Chloroflexi, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Other studies, using only broader "universal" primers, found much lower relative abundances in samples from the same sponge host species [19,28]. These differences may reflect natural biological variation, but could also be the result of reduced sensitivity due to amplification primer mismatches [1,9,12,29], raising concerns that historical surveys relying exclusively on unsuitable primers may have systematically under-reported Poribacteria abundance.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Other studies, using only broader "universal" primers, found much lower relative abundances in samples from the same sponge host species [19,28]. These differences may reflect natural biological variation, but could also be the result of reduced sensitivity due to amplification primer mismatches [1,9,12,29], raising concerns that historical surveys relying exclusively on unsuitable primers may have systematically under-reported Poribacteria abundance.…”
Section: Introductionmentioning
confidence: 98%
“…Ultrastructure and molecular characterization studies to date have relied heavily on samples obtained from a single host, Aplysina aerophoba, but Poribacteria-related 16S rRNA genes have also been detected in numerous other sponge genera, including Agelas, Astrosclera, Dactylospongia, Geodia, Ircinia, Plaktoris, Pseudoceratina, Rhabdastrella, Theonella, Vaceletia, and Xestospongia [2,[11][12][13][14][15][16][17][18][19]. Closely related 16S rRNA sequences have also been observed, albeit at much lower levels, in corals, seawater, and marine sediment samples [2,3,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNase-and DNase-free sterile tubes and tips were used in the operation to avoid contaminants from the environment. DNA in the RNA extractions was removed by a Turbo DNA-free kit (Ambion, Carlsbad, CA, USA) and was checked by PCR using universal primer 341F (5=-CCTAYGGGRBGCASCAG-3=) and reverse fusion primer 802R (5=-TACNVGGGTATCTAATCC-3=) targeting V3-V4 region of 16S rRNA genes (52). The primers were examined in Silva (https://www.arb -silva.de/) for primer coverage of Asgard archaea and novel bacterial phyla.…”
Section: Methodsmentioning
confidence: 99%
“…Raw paired-end reads were trimmed using Btrim (Kong, 2011) with default parameters and further assembled using FLASH with at least 40 bp overlap (Magoc and Salzberg, 2011). Assembled reads were subjected to QIIME 1.8.0 pipelines for downstream bioinformatics analysis (Caporaso et al, 2010) with the same modifications mentioned in our previous work (Gao et al, 2017). The SILVA database for taxonomic assignment was updated to version 128 .…”
Section: Prokaryotic Community Analysismentioning
confidence: 99%